2018
DOI: 10.1101/348771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NADP-dependent malic enzyme 1 participates in the abscisic acid response in Arabidopsis thaliana

Abstract: Arabidopsis thaliana possesses three cytosolic (NADP-ME1-3) and one plastidic (NADP-ME4) NADP-dependent malic enzymes. NADP-ME2 and-ME4 show constitutive expression, in contrast to NADP-ME1 and-ME3, which are restricted to particular tissues. Here, we show that NADP-ME1 transcript and protein were almost undetectable during normal vegetative growth, but gradually increased and reached levels higher than those of the other isoforms in the latest stages of seed development. Accordingly, in knockout nadp-me1 matu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The differential phenotypic response observed here is in line with previous reports suggesting specific roles for each Arabidopsis NADP‐ME isoform rather than redundancy of function (Maurino et al , ). NADP‐ME1 belongs to a particular phylogenetic group consisting of cytosolic NADP‐ME proteins of both monocotyledons and dicotyledons with C3, C4 or crassulacean acid metabolism (Gerrard Wheeler et al , ; Alvarez et al , ; Arias et al , ). It is likely that the isoforms belonging to this heterogeneous group are functionally conserved between species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential phenotypic response observed here is in line with previous reports suggesting specific roles for each Arabidopsis NADP‐ME isoform rather than redundancy of function (Maurino et al , ). NADP‐ME1 belongs to a particular phylogenetic group consisting of cytosolic NADP‐ME proteins of both monocotyledons and dicotyledons with C3, C4 or crassulacean acid metabolism (Gerrard Wheeler et al , ; Alvarez et al , ; Arias et al , ). It is likely that the isoforms belonging to this heterogeneous group are functionally conserved between species.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, cytosolic NADP‐ME1 (At2g19900) is localized in embryonic tissues and roots, while cytosolic NADP‐ME3 (At5g25880) is found mainly in trichomes and pollen (Gerrard Wheeler et al , ). Recently, NADP‐ME1 has been related to the abscisic acid response and protection against oxidative damage during seed storage, while its absence in knockout plants produced alterations in seed viability, germination and root architecture (Arias et al , ; Yazdanpanah et al , ). Here, we used a functional approach to analyze the involvement of NADP‐ME in Al tolerance using nadp‐me mutant lines treated with Al.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that ABA sensitivity is regulated by the expression of different genes involved in ABA perception/signaling. In studies using transgenic lines, overexpression of genes involved in ABA signaling such as the aspartic protease ASPG1, the NADP-malic enzyme or an E3 ubiquitin ligase enhanced tolerance to drought stress [25][26][27]. In another study, the loss of function through antisense regulation or by mutation of the receptor-like kinase1 (RPK1) in Arabidopsis decreased ABA sensitivity, stomatal closure and the expression of several stress-inducible genes such as LEAlike proteins, peroxidase, RD26, DnaJ-like protein, cytochrome P450 and SOD [28].…”
Section: Introductionmentioning
confidence: 99%
“…NADP-ME genes can be classified into photosynthetic and non-photosynthetic types. The former mostly function in the chloroplasts [13] and improve photosynthetic efficiency by facilitating the release of CO 2 from decarboxylation of malate in proximal bundle-sheath cells, and in C 4 plants by providing CO 2 to Rubisco for carbon fixation [14,15]. Genomic and phylogenetic analyses showed that the NADP-ME gene family in the Poaceae has four branches, with one branch (NADP-ME IV) being expressed in the plastids.…”
Section: Introductionmentioning
confidence: 99%